2002
DOI: 10.1074/jbc.m203977200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Flavins Promote Oxidative DNA Damage in Non-respiringEscherichia coli by Delivering Electrons to Intracellular Free Iron

Abstract: When cells are exposed to external H 2 O 2 , the H 2 O 2 rapidly diffuses inside and oxidizes ferrous iron, thereby forming hydroxyl radicals that damage DNA. Thus the process of oxidative DNA damage requires only H 2 O 2 , free iron, and an as-yet unidentified electron donor that reduces ferric iron to the ferrous state. Previous work showed that H 2 O 2 kills Escherichia coli especially rapidly when respiration is inhibited either by cyanide or by genetic defects in respiratory enzymes. In this study we esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
163
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(177 citation statements)
references
References 64 publications
12
163
1
1
Order By: Relevance
“…Expression of group I genes was inhibited by 6-AN, but not by electron transport inhibitors Hg 21 and CN 2 . The G6PDH inhibitor would inhibit NADPH production by G6PDH in the presence of Glc and hence would maintain a lower intracellular NADPH to NADP 1 ratio, whereas the direct (by Hg 21 ) or indirect (by CN 2 ) NADPH oxidation inhibitors would keep NADPH in a reduced state, which would maintain a higher intracellular NADPH to NADP 1 ratio (Woodmansee and Imlay, 2002). Thus, expression of group I genes is likely to be up-regulated by high cellular redox potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of group I genes was inhibited by 6-AN, but not by electron transport inhibitors Hg 21 and CN 2 . The G6PDH inhibitor would inhibit NADPH production by G6PDH in the presence of Glc and hence would maintain a lower intracellular NADPH to NADP 1 ratio, whereas the direct (by Hg 21 ) or indirect (by CN 2 ) NADPH oxidation inhibitors would keep NADPH in a reduced state, which would maintain a higher intracellular NADPH to NADP 1 ratio (Woodmansee and Imlay, 2002). Thus, expression of group I genes is likely to be up-regulated by high cellular redox potentials.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies ascorbic acid and glutathione, as well as NAD(P)H, ␣-keto acids, ferredoxin, O 2 . , and thioredoxin have been regarded as the intracellular reductants for Fe(III) (5,6,9,23). More recently, however, doubt arose whether these "classical" reductants are really responsible for the intracellular reduction of the metabolically and catalytically reactive iron, at least under certain conditions.…”
mentioning
confidence: 99%
“…More recently, however, doubt arose whether these "classical" reductants are really responsible for the intracellular reduction of the metabolically and catalytically reactive iron, at least under certain conditions. It has been proposed that as yet unidentified NAD(P)H-dependent redox enzymes can effectively reduce ferric ions to the ferrous state (23). More than 1 decade ago, Shi and Dalal (27) demonstrated that lipoyl dehydrogenase, a NAD(P)H-dependent flavoenzyme that often is denominated as diaphorase (26), is able to catalyze the one electron reduction of Cr(IV) and V(V).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NAD(P)H is known to be the main cellular electron donor for redox reactions and to provide electrons for the regeneration of different cellular antioxidants, which themselves are electron donors (reducing agents), such as glutathione and ascorbate. Thus cellular NAD(P)H content is a marker for the general reducing capacity of cells [19]. To monitor a possible influence of -glucose on the NAD(P)H content, we measured the cellular autofluorescence at λ exc l 365p12.5 nm and λ em l 450-490 nm, which is predominantly caused by NADH and NADPH [20].…”
Section: Effects Of D-glucose On the Cellular Reductive Statementioning
confidence: 99%